Artificial Intelligence in Agriculture: A Systematic Literature Review - Md. Ismail Hossen , Nafiz Fahad, Md. Ridoy Sarkar, Mohammad Ruhani Rabbi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this era, AI has a key role to make revolutionary changes in the field of Agriculture. In the past agricultural work was done manually with lots of difficulties and challenges. AI removed those difficulties by introducing automated systems for this reason nowadays artificial intelligence has a great impact on agriculture. The objectives are to present and gather information about AI’s use, challenges, and future. The systematic literature review is used for gathering and presenting the use of AI in agriculture. From the systematic literature review clear that the challenges and difficulties of agriculture are solved with the help of the application of artificial intelligence. Artificial intelligence automates soil management, disease management, crop monitoring, and weeding. The research helps humans to know how to use Artificial intelligence that’s why removes human difficulties in agriculture, and needs less manpower in agriculture works, researcher found compact information about the use of AI in agriculture to do more research.